Strategi Instagram Organik dan Berbayar untuk Brand Awareness pada Rebranding Program Studi - Jesye Octavia Nainggolan; Maresha Caroline Wijanto (Journal of Smart Technology and Engineering, 2026)
The rebranding process of the Master of Computer Science Program at Maranatha Christian University requires an effective communication strategy to increase brand awareness through Instagram. This study compares the performance of organic content and Instagram Ads based on Instagram Insights metrics, including reach, impressions, engagement rate, views, and profile activity, using a quantitative descriptive method through insights data documentation. The results show that Instagram Ads are more effective in expanding reach and rapidly increasing impressions, making them suitable for the early stage of rebranding. Meanwhile, organic content generates more stable and authentic engagement, supporting long-term image building and audience trust. Therefore, the recommended strategy is to combine Instagram Ads for initial awareness and consistent organic content to strengthen the program identity.